The Tourism Development Plan for Pua District, Nan Province / แผนพัฒนาการท่องเที่ยวอย่างยั่งยืน อำเภอปัว จังหวัดน่าน - รัดเกล้า เปรมประสิทธิ์, Rudklaw Pampasit / (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 1 (2556): January - June 2013DO - 10.14456/jcdr.v6i1.508, 2014)
ปัจจุบันการท่องเที่ยวอาเภอปัวมีแนวโน้มขยายตัวเพิ่มมากขึ้น จากความหลากหลายด้านการรองรับการท่องเที่ยว ไม่ว่าจะเป็นทางธรรมชาติ เรื่องราวทางประวัติศาสตร์ ประเพณีและวัฒนธรรม ประกอบกับนโยบายของรัฐ กลุ่มจังหวัด และจังหวัดที่ต้องการพัฒนาเมืองน่านให้เป็นเมืองท่องเที่ยว ทั้งนี้ การจัดทาแผนยุทธศาสตร์การพัฒนาการท่องเที่ยวจึงเป็นแนวทางหนึ่งที่องค์กรปกครองส่วนท้องถิ่นนามาใช้ในการสร้างและพัฒนากลไกเพื่อกาหนดทิศทางการพัฒนาการท่องเที่ยวอย่างยั่งยืน จากการกระจายอานาจตามประกาศคณะกรรมการการกระจายอานาจให้แก่องค์กรปกครองส่วนท้องถิ่น แผนการกระจายอานาจให้แก่องค์กรปกครองส่วนท้องถิ่น พ.ศ. 2551 (ฉบับที่ 2) บทความนี้มีวัตถุประสงค์เพื่อศึกษาแผนพัฒนา การท่องเที่ยวอย่างยั่งยืน อาเภอปัว จังหวัดน่าน ซึ่งเป็นแผนการทางานร่วมกันแบบบูรณาการระหว่างหน่วยงานส่วนภูมิภาคและองค์กรปกครองส่วนท้องถิ่น เพื่อพัฒนากลไกการพัฒนาการท่องเที่ยวเชิงพื้นที่ การศึกษาดังกล่าวทาการเก็บข้อมูลกับ 1) ผู้มีส่วนได้ส่วนเสียจากการท่องเที่ยว และ 2) เจ้าหน้าที่องค์กรปกครองส่วนท้องถิ่นและเจ้าหน้าที่หน่วยงานภาครัฐ โดยการสนทนากลุ่ม การสัมภาษณ์ และการเปิดรับฟังความคิดเห็น และนามากาหนดยุทธศาสตร์และแผนการพัฒนาการท่องเที่ยวอย่างยั่งยืน อาเภอปัว จังหวัดน่าน จากผลการศึกษากาหนดยุทธศาสตร์ได้ ดังนี้ 1) ยุทธศาสตร์การพัฒนาโครงสร้างพื้นฐานด้านกายภาพและสิ่งอานวยความสะดวกเพื่อการท่องเที่ยว ประกอบด้วย 3 แผนงาน 15 โครงการ 2) ยุทธศาสตร์การพัฒนาและฟื้นฟูแหล่งท่องเที่ยวให้เกิดความยั่งยืน ประกอบด้วย 2 แผนงาน 9 โครงการ 3) ยุทธศาสตร์การพัฒนาสินค้า บริการและการตลาดเพื่อส่งเสริมการท่องเที่ยว ประกอบด้วย 4 แผนงาน 15 โครงการ และ 4) ยุทธศาสตร์การส่งเสริมกระบวนการมีส่วนร่วมของภาครัฐ ภาคประชาชนและองค์กรปกครองส่วนท้องถิ่น ในการบริหารจัดการทรัพยากรการท่องเที่ยว ประกอบด้วย 2 แผนงาน 4 โครงการ อย่างไรก็ตาม เพื่อให้แผนพัฒนาการท่องเที่ยวอย่างยั่งยืน อาเภอปัว จังหวัดน่าน มีผลในเชิงปฏิบัติ มีข้อเสนอแนะคือ สานักงานท่องเที่ยวและกีฬาจังหวัดน่านร่วมกับองค์กรปกครองส่วนท้องถิ่นในพื้นที่ ควรเป็นเจ้าภาพหลักในการประสานงานกับหน่วยงานที่เกี่ยวข้อง เช่น การท่องเที่ยวแห่งประเทศไทย องค์การบริหารการพัฒนาพื้นที่พิเศษเพื่อการท่องเที่ยวอย่างยั่งยืน โรงพยาบาล สถานีตารวจ สถาบันการศึกษา ในการนาแผนงานดังกล่าวไปสู่การบูรณาการ ด้านงบประมาณและโครงการ เพื่อพัฒนากลไกการทางานร่วมกันแบบบูรณาการด้านการท่องเที่ยว คำสำคัญ: ยุทธศาสตร์ แผนพัฒนา การท่องเที่ยว Pua district recently has witnessed the tourism expansion thank to its diversity in tourism resources ranging from nature to culture. It also benefits from the state policies, made by the state, the provincial group and the province itself aiming to develop Nan province to be an alternative tourist destination. According to the Notification of the Decentralization Committee in the Decentralization to the Local Administration Plan B.E.2551 (2008) (No. 2), strategic planning for tourism is one option the local administrators can choose to create and develop the mechanism for controlling the direction of sustainable development. This paper aims to introduce the sustainable tourism development plan for Pua district, Nan province. This plan is a result of the integrated collaboration between the regional organizations and the local administrations to develop the mechanism for area based tourism development. Our study has collected information from 1) the stake holders in tourism industry and 2) the local administrative staff and the government officials by organizing focus group discussions, interviewing and conducting a public hearing. Then this study has been adopted as a basis for determining sustainable tourism strategies and development plans for Pua district, Nan province. These strategies includes 1) the strategic plan for developing the physical infrastructure and the facilities for tourism, composing of 3 plans and 15 projects, 2) strategic plan for sustainably developing and restoring the tourism destination, composing of 2 plans and 9 projects, 3) strategic plan for developing products, service and marketing plan to support the tourism, composing of 4 plans and 15 projects, and 4) strategic plan for promoting the participation of the public sector, the people sector and the local administrators in managing tourism resources, composing of 2 plans and 4 projects To effectively materialize the Tourism Development Plan for Pua district, Nan Provincial Office of Tourism and Sports (NPOTS) and the local administrations within the responsible area should be the key organizations to coordinate with other related organizations (such as the Tourism Authority of Thailand, the Designated Areas Sustainable Tourism Administration, the hospitals, the police stations, the education institutes etc.) for integrating the budget and the projects with the plans. This will lead to the development of mechanism for integrated collaboration in tourism. Keywords: Strategic, Development Plan, Tourism
Keywords: ยุทธศาสตร์ แผนพัฒนา การท่องเที่ยว Strategic, Development Plan, Tourism